2015
DOI: 10.3892/ijo.2015.2822
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated ING4/PTEN double tumor suppressor gene co-transfer modified by RGD enhances antitumor activity in human nasopharyngeal carcinoma cells

Abstract: Inhibitor of growth-4 (ING4) is a member of the inhibitor of growth (ING) family and acts as a tumor suppressor protein. PTEN is a phosphatase and shows potent and extensive antitumor activity. In this study, we constructed an RGD-modified bicistronic ING4/PTEN adenovirus (Ad.RGD-ING4-PTEN) and comprehensively investigated its effects following modification of the CNE human nasopharyngeal carcinoma cell line both in vitro and in vivo. We demonstrated that Ad.RGD-ING4-PTEN enhanced growth inhibition and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In lung cancer tissues, decreased ING4 expression is present in ~50% of cases and is associated with lymph node metastasis (29). Together with the results of other surveys, ING4 is a promising target in gene-radiotherapy (30)(31)(32).…”
Section: Discussionmentioning
confidence: 95%
“…In lung cancer tissues, decreased ING4 expression is present in ~50% of cases and is associated with lymph node metastasis (29). Together with the results of other surveys, ING4 is a promising target in gene-radiotherapy (30)(31)(32).…”
Section: Discussionmentioning
confidence: 95%
“…In colon cancer, PI3K/Akt/NF-κB pathway can be used as upstream factor to activate GLI1, while PI3K/Akt/NF-κB pathway is negatively regulated by PTEN (18,21). Previous studies have shown that ING4 is co-expressed with PTEN (22)(23)(24). In addition, ING5, a homologous protein of ING4, inhibits Akt activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…The most common modification in the fiber is the addition of an RGD sequence in the HI loop of the knob. This insertion enhances infection of cells that express high levels of α√β3/5 integrins, in particular, dendritic cells and cancer cells. …”
Section: Penton Complex Capsid Incorporationmentioning
confidence: 99%